The Effects of Foreign Direct Investment and Economic Growth on Environmental Degradation in Cameroon - Giyoh Gideon Nginyu; Gildas Dohba Dinga; Ndambi Caroline Bita (Law and Economy, 2024)
Developing countries, like Cameroon, usually face a dilemma between promoting economic growth and development and conserving their natural environment. Two key factors that influence this dilemma are foreign direct investment (FDI) and economic growth. Nowadays, it is obvious that sustainability is a vital development goal for every society. This study is designed to assess the effect of foreign direct investment (FDI) and economic growth on environmental degradation in Cameroon. Data for this study is gotten from the World Development Indicators and Environmental Footprint Network over the period 1961 to 2017. Based on a structural equation model technique, it was found that FDI has a negative and statistically significant effect on environmental sustainability, and economic growth has a negative and statistically significant effect on environmental sustainability. The Baron and Kenny approach reveals that there is partial mediation of economic growth on the effect of foreign direct investment on environmental degradation in Cameroon.